Fisiologi Pemrosesan Visual dan Faktor-faktor yang Memengaruhinya: Tinjauan Pustaka - Rani Himayani; Selvi Rahmawati; Nurul Utami; Zaki Ahmad Fauzan (Medula, 2021)
Humans use the sense of sight to recognize objects around them and manage the information these objects have. The process of managing information obtained from objects in the surrounding environment is referred to as visual processing. Visual processing includes several visual tasks, such as detecting the presence of objects, differentiating between objects, recognizing objects that are considered similar, identifying objects, pinpointing spatial locations, detecting their movements, colors and patterns, and making other types of decisions regarding visually complex events. . This process, which starts from light receiving by the optic part of the eye until cortical representations creation in the brain, is a complex process, and because of that, there are so many factors that can influence it. Among factors, there are factors that can optimize visual processing, such as emotional conditions, increased auditory orientation, and actions that accompany visual processes, as well as those that complicate visual processing, such as the aging process and the effects of premature birth. This understanding is important in determining the epidemiology of ocular disease and its influence in the diagnosis. of ocular disease.